Proporsi Asfiksia Neonatorum pada Kasus KPD dengan Non KPD di RSUD dr. Mohammad Soewandhi Surabaya: Proportion of Asphyxia Neonatorum in PROM Cases with Non PROM in RSUD dr. Mohammad Soewandhi Surabaya - Rufaida, Zulfa (Jurnal Kebidanan Midwiferia, 2016)
Severe fetal or asphyxia intrauterin can be a result of cord compression and repetitive due to prolonged reduction prolapsus amniotic fluid or umbilical cord. Complications are most common in PROM before 37 weeks gestation is respiratory distress syndrome (asphyxia), which occurs in 10-40% of new born babies. Risk of infection, disability, and death was also increased in the PROM events. This research methods, analytical case control study design. Inpartu mother population in maternity hospitals VK dr. Mohamad Soewandhie Surabaya in 2008 some 2101 cases. Sampling techniques proportional stratified random sampling. Large sample of 67 cases. Independent variable, premature rupture of membranes (PROM) and the dependent variable, neonates asphyxia. Instruments used data collection sheets. Sources of data from medical records. Analysis of data using non-parametric statistical approach Chi Square. The results of 33 cases of maternal inpartu that experience premature rupture of membranes (PROM), had 20.9% asphyxia and from were 34 cases of inpartu mothers who did not KPP, 20.9% experienced not asphyxia. Chi Square test results, X2arhitetic <X2table (1.802 <3.48) means that there is no difference in incidence neonates asphyxia in premature rupture cases (KPP) and no premature rupture of membranes (non – KPP). The conclusion of this study, less than 50% of inpartu mothers who experienced premature rupture of membranes (PROM), and more than 50% occurred asphyxia was, and there was no difference in incidence neonates asphyxia in premature rupture cases (KPP) and no premature rupture of membranes (non – KPP).